2018
DOI: 10.3389/fpsyg.2018.00163
|View full text |Cite
|
Sign up to set email alerts
|

Separability of Lexical and Morphological Knowledge: Evidence from Language Minority Children

Abstract: Lexical and morphological knowledge of school-aged children are correlated with each other, and are often difficult to distinguish. One reason for this might be that many tasks currently used to assess morphological knowledge require children to inflect or derive real words in the language, thus recruiting their vocabulary knowledge. The current study investigated the possible separability of lexical and morphological knowledge using two complementary approaches. First, we examined the correlations between voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 78 publications
6
17
0
Order By: Relevance
“…Moreover, based on their HMA performance, specifically on the HMA pseudo word task, we can infer that they have better understanding of morphological procedures, above and beyond specific lexical representation at the word level. This finding is a direct conformation of the proposal presented by Shahar Yames et al ( 2018 ), that suggested a separation of lexical and morphological knowledge among learners of additional language, who show much better performance on morphological tasks that are not dependent on extensive lexical knowledge, as measured in their case by pseudo word tasks. As further evidence of strong morphological awareness skills, the Arabic speakers performed within average range on EMA task (see footnote 3).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Moreover, based on their HMA performance, specifically on the HMA pseudo word task, we can infer that they have better understanding of morphological procedures, above and beyond specific lexical representation at the word level. This finding is a direct conformation of the proposal presented by Shahar Yames et al ( 2018 ), that suggested a separation of lexical and morphological knowledge among learners of additional language, who show much better performance on morphological tasks that are not dependent on extensive lexical knowledge, as measured in their case by pseudo word tasks. As further evidence of strong morphological awareness skills, the Arabic speakers performed within average range on EMA task (see footnote 3).…”
Section: Discussionsupporting
confidence: 84%
“…The fact that HMA pseudo can be the influential variable in EFL Total Narrative score is supported by numerous studies, that suggest strong relationship between MA and RC and MA and oral language development (Tomasello, 2005 ; Verhoeven, 2017 ). The choice of HMA pseudo as possible variable that may enhance the strength of the relationship between EFL skills and EFL narratives was dictated by the strong metalinguistic component of this particular task: manipulation of pseudo words implies strong knowledge of the underlying mechanism in creating appropriate morphosyntactic elements (Shahar Yames et al, 2018 ). Therefore, based on the assumption of the confounding hypothesis regarding the effect of a third variable in enhancing the relationship between the predictor and outcome variable, we wanted to see if HMA pseudo would have an effect on both, the ERC and Total narrative score.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current exploratory investigation, we included only a single measure of morphological awareness, tapping only one aspect of this meta-linguistic ability. Thus, this issue is ripe for a fuller investigation in future studies, which could include a wider array of morphological awareness and processing measures (e.g., Apel et al, 2013; Shahar-Yames et al, 2018). Along similar lines, because we only examined phonological and morphological awareness, we cannot determine at this stage whether phonological awareness in itself is an ability which influenced the consolidation, or alternatively, whether higher metalinguistic abilities of different kinds may also support efficient consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, morphological knowledge was not found to predict single word reading in the current study, although there is evidence that supports its recruitment in readers of English as an L2 (Casalis, Comissaire & Duncan, 2015;Diependaele, Duñabeitia, Morris & Keuleers, 2011, though see Silva & Clahsen, 2008, for conflicting results). In addition, morphological awareness and knowledge have also been linked to successful vocabulary acquisition in first (Sparks & Deacon, 2015) and second language (Shahar-Yames, Eviatar & Prior, 2018). Therefore, it might also be advisable to increase attention to morphological patterns, and specifically as they relate to accurate reading, within the EFL curriculum.…”
Section: Pedagogical Implications For Efl Instructionmentioning
confidence: 99%